Chard extract increased gastric sialic acid and ameliorated oxidative stress in valproic acid-administered rats - ALTURFAN, EBRU IŞIK; AKBAY, TUĞBA; YARAT, AYŞEN (My University, 2023)
Valproic acid, one of the most used drugs for epilepsy patients, has some known side effects. Chard extract has many pharmacological activities. The study aims to evaluate whether valproic acid might interfere with oxidative metabolism in gastric tissue and whether chard ameliorates these effects. The Sprague Dawley rats were divided into four groups (n=8); control, chard-given control, valproic acid, and chard-given valproic acid. The aqueous extracts of chard leaves were given 1 h before the administration of valproic acid for 7 days. On the 8th day, the animals were sacrificed under anesthesia and gastric tissues were homogenized. When compared to the control group, valproic acid significantly increased malondialdehyde and catalase activity, while superoxide dis- mutase activity decreased. Chard administration increased glutathione and, sialic acid levels and decreased malondialdehyde levels and superoxide dismutase activity in the valproic acid group. Based on these findings, since chard increased gastric sialic acid levels, we may suggest that chard may protect gastric mucosa may be through its antioxidant effects.
Keywords: BESLENME VE DİYETETİK; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); NUTRITION & DIETETICS; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); food and nutrition literacy; questionnaire development; Chinese adults; validation; HEALTH LITERACY; DISEASE; VALIDITY; DIETARY; ood and nutrition literacy; questionnaire development; Chinese adults; validation